PROBLEMATIKA GURU DALAM PENGEMBANGAN MEDIA PEMBELAJARAN SEJARAH - Vinny Raihany; Shaffia Darma Widjaya; Rinita Meliya; Andi Andi (Universitas Negeri Malang, 2022)
This research can be a reference for teachers in the use and development of historical learning media in order to achieve effective, efficient, creative, and innovative learning objectives. The use and development of learning media is also a must for every teacher so that it helps in clarifying learning materials and arouses students' interest and motivation in learning history. This study used qualitative research methods. The sources that are used as references in this research are scientific journals, scientific articles, and interviews that are related to research. Identification of problems in this study are 1) History teachers have not been able to develop and utilize history learning media, meaning that history teachers have not been able to use learning media in accordance with learning objectives. 2) The history teacher has not used various types of media, meaning that the teacher does not know and understand the various types of media that can be used in accordance with the learning material. 3) The lack of teacher knowledge on the use of technology in history learning means that teachers are not yet competent in using various types of designs and various types of media with the help of technology. 4) History teachers are less creative and innovative in the use of media for history learning, meaning that teachers have not been able to work in using media.Penelitian ini dapat menjadi acuan bagi guru dalam penggunaan dan pengembangan media pembelajaran sejarah untuk mencapai tujuan pembelajaran yang efektif, efisien, kreatif, dan inovatif. Penggunaan dan pengembangan media pembelajaran juga merupakan suatu keharusan bagi setiap guru sehingga membantu dalam memperjelas materi pembelajaran dan membangkitkan minat dan motivasi siswa dalam belajar sejarah. Penelitian ini menggunakan metode penelitian kualitatif. Sumber yang dijadikan referensi dalam penelitian ini adalah jurnal ilmiah, artikel ilmiah, dan wawancara yang berkaitan dengan penelitian. Identifikasi masalah dalam penelitian ini adalah 1) Guru sejarah belum mampu mengembangkan dan memanfaatkan media pembelajaran sejarah, artinya guru sejarah belum mampu menggunakan media pembelajaran yang sesuai dengan tujuan pembelajaran. 2) Guru sejarah belum menggunakan berbagai jenis media, artinya guru belum mengetahui dan memahami berbagai jenis media yang dapat digunakan sesuai dengan materi pembelajaran. 3) Kurangnya pengetahuan guru tentang pemanfaatan teknologi dalam pembelajaran sejarah menyebabkan guru belum kompeten dalam menggunakan berbagai jenis desain dan berbagai jenis media dengan bantuan teknologi. 4) Guru sejarah kurang kreatif dan inovatif dalam penggunaan media untuk pembelajaran sejarah, artinya guru belum bisa bekerja dalam menggunakan media.